Children’s bond with companion animals and associations with psychosocial health: A systematic review - Groenewoud, Daniëlle; Enders-Slegers, Marie-Jose; Leontjevas, Roeslan; van Dijke, Annemiek; de Winkel, Tynke; Hediger, Karin (Frontiers in Psychology, 2023)
Background Companion animals can fulfill children’s attachment needs. A secure attachment to humans is positively associated with psychosocial health, therefore, the extent to which this applies to a strong child-companion animal bond is worth examining. Aims We aimed to gain insight into the current literature regarding the bond between children and companion animals and psychosocial health. Secondary, we also synthesized evidence about the (1) characteristics of children and companion animals and the strength of their bond; (2) the correlations between attachment to humans and the child-companion animal bond; and (3) the instruments used to measure the child-companion animal bond. Method According to PRISMA guidelines, we searched three major electronic databases (PubMed, EBSCOhost, and Web of Science) in September 2021 and included records with the following criteria: peer reviewed English articles with quantitative and qualitative data on child-companion animal bonds and children’s psychosocial health. Reports with participants younger than 18 years of age with a family owned companion animal were included. Two authors performed the screening and determined eligibility according to a predefined coding protocol. Results The search revealed 1,025 unique records, of which we included 29 studies. Some positive associations were reported between the strength of the child-companion animal bond and children’s psychosocial health outcomes like empathy, social support, and quality of life, although some results were contradictory. We found differences in associations between a child’s gender, companion animal species and the strength of the child-companion animal bond. A secure attachment style to parents was positively associated with a stronger child–companion animal bond. Most of the instruments currently used, measure the strength of the bond. Discussion This review suggests that the child-companion animal bond could be beneficial for children’s psychosocial health, but some results were inconclusive. Also, not every relationship develops into an attachment. Since a strong bond with animals might not be the same as a secure attachment, we advise to modify human attachment instruments, in order to effectively study children’s attachment to companion animals. Lastly, research designs that are able to investigate the causality of the relationship between the child-companion animal bond and psychosocial health are required.